2017
DOI: 10.5830/cvja-2016-043
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum cardiomyopathy among cardiovascular patients referred for echocardiography at Parirenyatwa Teaching Hospital, Harare, Zimbabwe

Abstract: SummaryObjectivesThe main aim was to evaluate the outcome of patients with peripartum cardiomyopathy (PPCM) within six months of diagnosis. The secondary aim was to describe demographic and clinical characteristics of patients with PPCM in Harare, Zimbabwe.MethodsThis was a prospective cohort study in which patients recruited into a detailed PPCM registry were followed up for six months. Echocardiograms were performed at enrolment, and three and six months after diagnosis, to determine left ventricular functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…This finding of mild disease severity in our study cohort starkly contrasts with what has been observed in other African studies. Studies conducted in Zimbabwe [ 26 ], Togo [ 27 ] and South Africa [ 17 , 18 , 21 ] reported about 46.5%, 77% and 66.7–89% of patients with PPCM presenting in NYHA functional class III/IV at baseline respectively. A high proportion of patients with PPCM presenting in NYHA functional class III or IV (68.8%) was also reported by a multi-country study investigating clinical characteristics of patients with PPCM in Africa, Middle East, Asia and Europe [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This finding of mild disease severity in our study cohort starkly contrasts with what has been observed in other African studies. Studies conducted in Zimbabwe [ 26 ], Togo [ 27 ] and South Africa [ 17 , 18 , 21 ] reported about 46.5%, 77% and 66.7–89% of patients with PPCM presenting in NYHA functional class III/IV at baseline respectively. A high proportion of patients with PPCM presenting in NYHA functional class III or IV (68.8%) was also reported by a multi-country study investigating clinical characteristics of patients with PPCM in Africa, Middle East, Asia and Europe [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…EURObservational Research Programme (EORP), an ongoing registry for patients with PPCM presented with thrombo-embolic events (6.8%) [ 28 ]. A higher prevalence of co-existing intra-cardiac thrombus of 9.3% and 16.7% was documented in a study in Zimbabwe [ 26 ] and South Africa respectively [ 21 ]. Thrombo-embolic events are also associated with a high risk of mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations